(untitled) (Research, Society and Development, 2021)
The experience report aims to report the use of WhatsApp Messenger for educational practice in health with school adolescents. It is a qualitative study, developed from July to September 2020, on WhatsApp Messenger, with 20 adolescents from two high schools in Sobral-Ceará, Brazil. Educational technologies in health were built in order to provide health information and foster dialogue with adolescents about the use of psychoactive substances. However, the adolescents did not participate in the intervention moments as expected. However, WhatsApp Messenger can be used for educational purposes with school teenagers, allowing the sharing of files (videos, photos, documents, among others) and dialogue between participants.